P22-44 Estrogenic activity of nanoplastics in vitro - N. Peranić; L. Božičević; K. Altmann; J. Hildebrandt; R. Portela; M. Banares; I. Vinković Vrček (Toxicology Letters, 2025)

P21-65 Androgenic and anti-androgenic effects of nanoplastics - N. Peranić; L. Božičević; K. Altmann; J. Hildebrandt; R. Portela; M. Banares; I. Vinković Vrček (Toxicology Letters, 2024)

P15-02 Assessing immune-related effects of nanoplastics on primary human monocytes in vitro - N. Negi; H. Hjertholm; M. Lislien; N.M. Smith; D. Behmen; K. Altmann; J. Hildebrandt; M. Andreassen; B.B. Granum; R. Pieters; H. Dirven; I. Snapkow (Toxicology Letters, 2024)

S04-01 Inflammation-related key events stimulated by micro- and nanoplastics - A. van den Berg; K. Adriaans; E. Hoppener; L. Parker; A. Boersma; K. Altmann; J. Legler; R. Pieters (Toxicology Letters, 2024)

Development of the prosencephalic structures, ganglionic eminence, basal ganglia and thalamus at 11 + 3 to 13 + 6 gestational weeks on 3D transvaginal ultrasound including normative data - R. Altmann; T. Rechberger; C. Altmann; L. Hirtler; I. Scharnreitner; P. Stelzl; S. Enengl (Brain Structure and Function, 2023)
Objectives To show the development of ganglionic eminence, basal ganglia and thalamus/hypothalamus in week 11 + 3 to 13 + 6 by transvaginal 3D ultrasound. Methods To visualize the prosencephalic structures surrounding the 3rd ventricle, 285 three-dimensional ultrasound volume blocks from 402 fetuses examined were selected in a prospective transvaginal 3D study to compare ultrasound images of ganglionic eminence, basal ganglia, thalamus/hypothalamus with embryological sections. In addition, measurements of the described structures were made in 104 fetuses to quantify the embryological development. Results The sonomorphologic characteristics of ganglionic eminence, basal ganglia and thalamus/hypothalamus are described in 71% of the fetuses examined. Measurements of the structures in 57% of the fetuses, show the following results: axGE ap = 0.17 + 0.112*CRL; axGE/I = 0.888 + 0.048*CRL; axGE/BG = 0.569 + 0.041*CRL; coGE/BG = 0.381 + 0.048*CRL; coTh lat = − 0.002 + 0.135*CRL; coTh/HyT = 3.68 + 0.059*CRL; co3.V lat = 0.54 + 0.008*CRL. Conclusion Transvaginal 3D neurosonography allows visualization and measurement of normal structures in the fetal prosencephalon at 11 + 3 to 13 + 6 weeks of gestation (GW) including details of ganglionic eminence (GE), basal ganglia (BG), and thalamus/hypothalamus (Th/HyT). Further scientific work is needed before using the results to decide on pathological changes in patients.

Early childhood lead exposure is not reflected in adult bone lead: Results of a sub-cohort of African American women in the Cincinnati lead study - David R. Chettle; Kim N. Dietrich; Amit Bhattacharya; Heidi J. Kalkwarf; Lorenna Altmann; Chi Wei; Cyndy Cox; Jun Ying (Environmental Research, 2023)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Multi-omics-based prediction of hybrid performance in canola - Dominic Knoch; Christian R. Werner; Rhonda C. Meyer; David Riewe; Amine Abbadi; Sophie Lücke; Rod J. Snowdon; Thomas Altmann (Theoretical and Applied Genetics, 2021)
Key message Complementing or replacing genetic markers with transcriptomic data and use of reproducing kernel Hilbert space regression based on Gaussian kernels increases hybrid prediction accuracies for complex agronomic traits in canola . In plant breeding, hybrids gained particular importance due to heterosis, the superior performance of offspring compared to their inbred parents. Since the development of new top performing hybrids requires labour-intensive and costly breeding programmes, including testing of large numbers of experimental hybrids, the prediction of hybrid performance is of utmost interest to plant breeders. In this study, we tested the effectiveness of hybrid prediction models in spring-type oilseed rape ( Brassica napus L./canola) employing different omics profiles, individually and in combination. To this end, a population of 950 F 1 hybrids was evaluated for seed yield and six other agronomically relevant traits in commercial field trials at several locations throughout Europe. A subset of these hybrids was also evaluated in a climatized glasshouse regarding early biomass production. For each of the 477 parental rapeseed lines, 13,201 single nucleotide polymorphisms (SNPs), 154 primary metabolites, and 19,479 transcripts were determined and used as predictive variables. Both, SNP markers and transcripts, effectively predict hybrid performance using (genomic) best linear unbiased prediction models (gBLUP). Compared to models using pure genetic markers, models incorporating transcriptome data resulted in significantly higher prediction accuracies for five out of seven agronomic traits, indicating that transcripts carry important information beyond genomic data. Notably, reproducing kernel Hilbert space regression based on Gaussian kernels significantly exceeded the predictive abilities of gBLUP models for six of the seven agronomic traits, demonstrating its potential for implementation in future canola breeding programmes.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Dent and Flint maize diversity panels reveal important genetic potential for increasing biomass production - R. Rincent; S. Nicolas; S. Bouchet; T. Altmann; D. Brunel; P. Revilla; R. A. Malvar; J. Moreno-Gonzalez; L. Campo; A. E. Melchinger; W. Schipprack; E. Bauer; et al. (Theoretical and Applied Genetics, 2014)

Molecular cloning of cDNA encoding N-acetylglucosaminyltransferase II from Arabidopsis thaliana - R. Strasser; H. Steinkellner; M. Borén; F. Altmann; L. Mach; J. Glössl; J. Mucha (Glycoconjugate Journal, 1999)

Fate and effects of micropollutants in the Gironde estuary, France: a multidisciplinary approach - C. Amiard-Triquet; S. Altmann; J. C. Amiard; C. Ballan-Dufrançais; P. Baumard; H. Budzinski; C. Crouzet; P. Garrigues; E. His; A. Y. Jeantet; R. Menasria; P. Mora; et al. (Hydrobiologia, 1998)

Cadmium mobilisation under conditions simulating anaerobic to aerobic transition in a landfill leachate-polluted aquifer - R. Scott Altmann; Alain C. M. Bourg (Water, Air, & Soil Pollution, 1997)

CADMIUM MOBILISATION UNDER CONDITIONS SIMULATING ANAEROBIC TO AEROBIC TRANSITION IN A LANDFILL LEACHATE-POLLUTED AQUIFER - R. SCOTT ALTMANN; ALAIN C. M. BOURG (Water, Air, & Soil Pollution, 1997)